PENGARUH CORPORATE GOVERNANCE TERHADAP TRIPLE BOTTOM LINE REPORTING - Datillah, Rahmat; Zaitul, Zaitul; Ilona, Desi (POLITEKNIK LP3I JAKARTA, 2023)
The importance of the triple bottom line (TBL) concept has been debated among academicians and practitioners. The discussion about the extent of implementing these sustainable initiatives and what factor determines its reporting. Corporate governance is one of the influencing factors of TBL reporting. However, limited studies investigate corporate governance's role in TBL reporting, especially utilizing data from different continental European corporate governance systems like Indonesia. Therefore, this paper investigates the effect of the commissioner board size and gender on TBL reporting using the coal-mining industry. In addition, this study also collected the company's characteristic data and included it in the research model to maintain the model specification error. Twenty coal mining company has participated in this study. The analysis of multivariate regression is employed, and the finding indicates that there is no corporate governance role proxied by the size and gender of the commissioner's board. However, profitability is positively related to all dimensions of TBL. In addition, the TBL (social and environmental) is influenced positively by the company size. This study has practical and theoretical implications and is discussed in detail. Keywords: Triple Bottom Line, Board Of Commissioners’ Size, Existence Of Women